The Role of School Climate in Physical Education: Scientometric Analysis - Suwarni, Suwarni; Perdima, Feby (Yayasan Sembilan Pemuda Indonesia, 2025)
By analyzing author keywords, visualizing citation patterns, and assessing the effectiveness of research on school climate in physical education, this study attempts to provide a thorough picture of the descriptive aspects of publications. ScientoPy software was utilized in the study to examine the quantity of publications, top research areas, most proactive authors, author keywords, well-liked sources, and institutional data. This study used 350 entries from the Scopus database and followed data reconciliation. Growing trends in school climate research and physical education are shown by the Scopus database. With 19 published documents, “Physical Education and Sport Pedagogy” is recognized as the most active scientific resource. The term “physical education” has become more well-liked. Physical education, motivational climate, motivation, physical activity, and achievement goal theory were the top five search terms in this survey. The primary research fields, keywords, connected studies, and most esteemed organizations and researchers in school climate research and physical education have been identified by this study. The study also offers a global perspective on the current hot themes of physical education and school climate to readers and scholars in the future. Additionally, it provides a variety of analyses to assist in organizing data in order to develop theory and put into practice rigorous school climate research and physical education.